An analytical force and energy model for ductile-brittle transition in ultra-precision grinding of brittle materials. (15th April 2022) - Zheng, Zhengding; Huang, Kai; Lin, Chuangting; Zhang, Jianguo; Wang, Ke; Sun, Peng; Xu, Jianfeng
Highlights: Multiple grain interaction states were explored by actual grain protrusion heights and random grain distribution. The surface generation mechanisms of the ductile-brittle transition was revealed based on multiple grains random interactions. An analytical grinding force and energy model was developed to predict the critical grinding depth of brittle-ductile transition. The influence rules of grinding conditions on the critical grinding depths were obtained for grinding process optimization and quality control. Abstract: The critical grinding depth of ductile-brittle transition is an important processing parameter to guarantee brittle materials machining in ductile mode. Nevertheless, it is a difficult task to predict the critical grinding depth considering multiple grain interactions due to the random grain distribution on the wheel. In our paper, a novel grinding force and energy model is established to predict the critical grinding depth with considering the random interactions between multiple grains, and experimental validations are carried out on single crystal silicon. In this process, the grain-workpiece interactions are explored by the actual grain protrusion heights and random grain distribution. The surface generation mechanisms of the ductile-brittle transition are comprehensively investigated by applying the numerical and experimental methods. It shows that the plastic ploughing and brittle fracture are the dominant material removal modes when grinding brittle materials. Moreover, validation experiment results indicate that the proposed model could accurately predict the realistic critical grinding depth with an average deviation of less than 9.2%. Finally, based on the proposed model, the influence of grinding conditions on the critical grinding depth are investigated in detail. The critical grinding depth increases with increasing grinding speed, while decreases with increasing feed speed. Hence, this research not only provides a new method for predicting the critical grinding depth, but also enhances the understanding of the ductile-brittle transition mechanism in brittle materials machining. Graphical abstract: Image, graphical abstract